Abnormal Return and the Charactersitics of Merger and Acquisition in Indonesia - Gisella, Luh Putu Gina; Chalid, Dony Abdul (Journal of Economics, Business, and Accountancy Ventura, 2017)
Indonesia also have  experienced the practice of Merger and Acquisition (M & A) transaction, like other parts of the world. This study  aims to see if there are abnormal returns for the acquirer companies in M&A transactions that occurred in Indonesia, and also to test if there are some characteristics related to M&A that affects the abnormal returns. This study uses 143 M & A transaction data public company in Indonesia in 2005 until 2014. Event-study analysis was also conducted to find acquirer abnormal stock return around the announcement of M & A. In addition,  OLS regression was also conducted to find whether the cash payment method in the M & A negatively affects the abnormal return. The  condition of companies (Net Profit Margin, Sales Growth, firm value) also affect the abnormal return. This shows that the method of payment and acquire companies’ conditions have effects on the perception of investors towards M & A transactions that occured.